2017
DOI: 10.1108/imefm-11-2015-0144
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure in a tax-free economy: evidence from UAE

Abstract: Purpose This paper aims to investigate the determinants of capital structure for non-financial listed firms in the United Arab Emirates (UAE) for the period 2004-2010. The contradiction between the different capital structure theories, limited literature on UAE and its distinctive characteristic of tax-free environment were the motivation for this paper. Design/methodology/approach The authors used two panel data techniques to estimate the regression models, and a series of robustness checks. Findings The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
7
10
1
5
Order By: Relevance
“…Confirming earlier studies in emerging countries specifically Middle East countries (Omet and Mashharawe, 2004;Qureshi, 2009;Sheikh and Qureshi, 2014;Abdulla, 2017;Kumar, Colombage & Rao, 2017), the results display that firms prefer the use of equity financing their projects and debt is easily available for experienced firms with preference of the use of short-term debt over long-term debt. Further, these firms follow a mix of two capital structure theories: trade-off theory and pecking order theory; while little evidences support the agency cost theory.…”
Section: Introductionsupporting
confidence: 87%
“…Confirming earlier studies in emerging countries specifically Middle East countries (Omet and Mashharawe, 2004;Qureshi, 2009;Sheikh and Qureshi, 2014;Abdulla, 2017;Kumar, Colombage & Rao, 2017), the results display that firms prefer the use of equity financing their projects and debt is easily available for experienced firms with preference of the use of short-term debt over long-term debt. Further, these firms follow a mix of two capital structure theories: trade-off theory and pecking order theory; while little evidences support the agency cost theory.…”
Section: Introductionsupporting
confidence: 87%
“…The previously empirical research conducted by Tong & Green (2005), Zhang & Kanazaki (2007) Abdulla (2017), found out that profitability has a negative effect on the company capital structure. The negative effect between profitability and the capital structure means when the company profitability increases, then the proportion of the debt used in the capital structure will decrease because the company will prioritize the internal funding first.…”
Section: Hypotheses Developmentmentioning
confidence: 98%
“…The empirical research by Chiang, Chen, & Lam (2010), Sugianto (2013) Chadha & Sarma 2015, and Abdulla (2017) found out that tangibility assets affect the capital structure. The result of the research conducted shows that tangibility assets have a unidirectional relationship with the capital structure of the company.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In this way, firms with a considerable percentage of a liquid asset have a greater ability to meet up their financial commitments as at when due. Thus, resulting in the prediction that highly liquid firms issue fewer debt instruments when rebalancing their capital structure (Abdulla, 2017;Al-Najjar, 2011;Rokhayati, Pramuka, & Sudarto, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%